Influence of different curing methods on the compressive strength of ultra-high-performance concrete : A comprehensive review - Hamada, Hussein Mahmood; Alattar, Alyaa; Tayeh, Bassam A.; Fadzil, Mat Yahaya; Almeshal, Ibrahim (Elsevier Ltd, 2022)
Ultra-high-performance concrete (UHPC) is a distinguishing material used in new construction and conjunction with conventional concrete. However, some issues limit the wider application of UHPC, such as high autogenous shrinkage, low workability for large-volume production, high cost, and unpredictable peak curing method. This comprehensive study aims to clarify the different effects of curing methods on the strength development of normal concrete and UHPC. The present article reviews studies that used microwave curing, autoclave curing, carbon curing, steam curing, electric curing, ambient and air curing and water to determine their effect on compressive strength. All the curing methods achieved satisfactory values of compressive strength. However, it is not practical to specify the peak curing regimes for concrete or UHPC since the best results need critical monitoring of curing parameters. The time when the samples are demolded and subjected to hydrothermal and thermal treatments varies in the literature since it depends on the binder setting time. That time should be carefully selected to avoid adverse effects and to maximise output. A combination of these curing regimes could be used together or with pressure or heat to further improve the compressive strength. In addition to the type of materials used, the curing temperature and duration significantly affect the overall performance of concrete. This review is expected to guide future research and provide an overview of the research field.